Brief communication: Evolution of a specific O allele (O1vG542A) supports unique ancestry of Native Americans. Issue 4 (18th July 2013) - Villanea, Fernando A.; Bolnick, Deborah A.; Monroe, Cara; Worl, Rosita; Cambra, Rosemary; Leventhal, Alan; Kemp, Brian M.
ABSTRACT In this study, we explore the geographic and temporal distribution of a unique variant of the O blood group allele called O1vG542A, which has been shown to be shared among Native Americans but is rare in other populations. O1vG542A was previously reported in Native American populations in Mesoamerica and South America, and has been proposed as an ancestry informative marker. We investigated whether this allele is also found in the Tlingit and Haida, two contemporary indigenous populations from Alaska, and a pre‐Columbian population from California. If O1vG542A is present in Na‐Dene speakers (i.e., Tlingits), it would indicate that Na‐Dene speaking groups share close ancestry with other Native American groups and support a Beringian origin of the allele, consistent with the Beringian Incubation Model. If O1vG542A is found in pre‐Columbian populations, it would further support a Beringian origin of the allele, rather than a more recent introduction of the allele into the Americas via gene flow from one or more populations which have admixed with Native Americans over the past five centuries. We identified this allele in one Na‐Dene population at a frequency of 0.11, and one ancient California population at a frequency of 0.20. Our results support a Beringian origin of O1vG542A, which is distributed today among all Native American groups that have been genotyped in appreciable numbers at this locus. This result is consistent with the hypothesis that Na‐Dene and other Native American populations primarily derive their ancestry from a single source population. Am J Phys Anthropol 151:649–657, 2013. © 2013 Wiley Periodicals, Inc.